2021
DOI: 10.1007/s11325-021-02350-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of simplified-cognitive behavioral therapy for insomnia(S-CBTI) among female COVID-19 patients with insomnia symptom in Wuhan mobile cabin hospital

Abstract: Background The outbreak of Coronavirus Disease-2019 (COVID-19) caused great psychological distress often with comorbid insomnia. Insomnia is common in patients with COVID-19 admitted to mobile cabin hospitals. Insomnia may lead to immune dysfunction, a condition not conducive to recovery from COVID-19. The use of sedative-hypnotic drugs is limited by their inhibitory effect on the respiratory system. A paucity of research is available regarding psychotherapy interventions to improve insomnia symptoms among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 27 publications
0
17
0
5
Order By: Relevance
“…Zur Vervollständigung wird es dennoch aufgeführt. Zur Verbesserung von Schlafstörungen kann auch kognitive Verhaltenstherapie genutzt werden 45 53 .…”
Section: Methodeunclassified
See 1 more Smart Citation
“…Zur Vervollständigung wird es dennoch aufgeführt. Zur Verbesserung von Schlafstörungen kann auch kognitive Verhaltenstherapie genutzt werden 45 53 .…”
Section: Methodeunclassified
“…Die Auswertung der klinischen Studien und Übersichtsarbeiten weist auf eine hohe Bedeutung der kognitiv-therapeutischen Ansätze bei der Rehabilitation von Patienten und Patientinnen mit Long-COVID hin. Aktuelle Studien zur Wirksamkeit von verhaltenstherapeutischen Konzepten bei subjektiver Belastung der Betroffenen durch Angst-und Depressionssymptomen [57,58], Schlafstörungen [45,53], Stressbelastung [73], Fatigue [70] und posttraumatischer Belastungsstörung [24,25], geben erste Hinweise. Multimodale Behandlungsansätze sollten daher bei Persistenz angedacht werden.…”
Section: Symptombezogene Pathways Für Die Multiprofessionelle Und Int...unclassified
“…Although the current result indicates that the report of anxiety and depression was below 25% nevertheless those women who are struggling with such symptoms could benefit from online therapeutic interventions such as CBT-I ( Heet al, 2021 ) as well as local tell-counselling services. Mitigating and addressing mental health symptoms is a priority, particularly in pandemics where risks of isolation and health hazards are elevated, left untreated could lead to serious implications.…”
Section: Conclusion and Recommendationsmentioning
confidence: 58%
“…Thus, the prevention and treatment of insomnia, per se, as well as insomnia symptoms in addition to psychological issues should be prioritized. Results of a recent clinical trial during the COVID-19 pandemic concluded that insomnia symptoms could be improved with simplified CBTi, particularly for stress-related acute insomnia [ 61 ]. In addition, a task force of the European CBTi academy has made clinical practice guidelines specifically to reduce the burden of stress-related insomnia [ 62 ].…”
Section: Discussionmentioning
confidence: 99%